PROGNOSTIC AND PREDICTIVE SIGNIFICANCE OF MEASURABLE RESIDUAL DISEASE IN ACUTE MYELOBLASTIC LEUKEMIA - Rajić, Jovan; Milošević, Violeta; Gunjak, Tara; Kraguljac-Kurtović, Nada; Bogdanović, Andrija; Virijević, Marijana; Suvajdžić-Vuković, Nada; Mitrović, Mirjana; Pravdić, Zlatko; Vlajin, Stevan; Igić, Milan; Vidović, Ana (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Acute myeloblastic leukemia (AML) is an umbrella term for a heterogeneous group of clonal neoplastic diseases of hematopoietic cells. Detecting residual leukemic cells (measurable residual disease – MRD) is the most important prognostic and predictive factor in AML. The aim: The study aims to analyze the effect of administered chemotherapy based on the results of MRD testing in patients with AML treated at the University Clinical Center of Serbia (UCCS) Clinic for Hematology. Materials and Methods: Our study included the analysis of 111 AML patients, treated between January 2020 and January 2024. All diagnostic procedures performed were based on the most recent recommendations of European LeukemiaNet (ELN). Results: MRD+ patients who continued treatment with intensive chemotherapy (CHT), using full doses of 3+7 CHT as reinduction therapy, had a significantly longer remission (complete remission – CR) and a longer overall survival (OS). The duration of CR (p = 0.004) and OS (p = 0.019) were statistically significantly longer in patients who maintained a negative MRD status at the end of treatment. In transplanted patients, overall survival (OS; p = 0.006) and duration of remission (CR; p = 0.002) were significantly longer (median: OS 20 months; CR 21 months), as compared to the group of non-transplanted patients (median: OS 13 months; CR 8 months). Discussion: Measurable residual disease (MRD) can be both prognostic and predictive. However, the absolute measurable level of the disease is not the only determinant of the patient’s outcome, since the biology of AML, as well as other clinical patient-related factors (age, comorbidities, various complications of applied chemotherapy, especially infections), modify the risk associated with MRD test results. Conclusion: The study has demonstrated the great importance of timely detection of MRD, as well as the appropriateness of applying more intensive CHT in MRD-positive patients, along with continued treatment with allogeneic hematopoietic stem cell transplantation.